2022
DOI: 10.1088/1742-6596/2300/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Directional transport of droplets impacting on superhydrophobic opening triangular groove surfaces

Abstract: Directional droplet transport is of great importance to various processes including heat transfer, water harvesting and microfluidics. Here, a facile superhydrophobic opening triangular groove surface was proposed, and the directional transport behavior of droplets impacting on the surface was observed. The results show that the essence of the directional transport on the opening triangular groove surface can be attributed to the interaction between the impinging droplet and the groove sidewall, and the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Wang et al 27 identified the factors affecting the distance of transport and provided guidelines for wedge‐shaped design for optimized spontaneous liquid transport. It is confirmed that wedge angle and groove depth are two important indicators of wedge‐shaped structures 28 . Similar to superhydrophobic surfaces, water droplets also show behaviors such as deposition, total bounce, and splashing on impact on SLIPS 29,30 .…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Wang et al 27 identified the factors affecting the distance of transport and provided guidelines for wedge‐shaped design for optimized spontaneous liquid transport. It is confirmed that wedge angle and groove depth are two important indicators of wedge‐shaped structures 28 . Similar to superhydrophobic surfaces, water droplets also show behaviors such as deposition, total bounce, and splashing on impact on SLIPS 29,30 .…”
Section: Introductionmentioning
confidence: 62%
“…Wang et al 27 that wedge angle and groove depth are two important indicators of wedge-shaped structures. 28 Similar to superhydrophobic surfaces, water droplets also show behaviors such as deposition, total bounce, and splashing on impact on SLIPS. 29,30 A basic question that arises if one wants to use SLIPS for surface cleaning is as follows: is there a possibility to control the self-transport behavior of droplets on SLIPS with wedge-shaped structures?…”
Section: Introductionmentioning
confidence: 99%